At a meeting of the freeholders and other inhabitants of the town of Boston : legally qualified and warn'd in public town meeting assembled, at Faneuil-Hall, on Monday the 12th of September, A.D. 1768 ([publisher not identified], 1768)
Motions and resolves in response to expectations that British troops would be quartered in Boston, and that the royal governor would receive no instructions for convening the General Court. Calling for a provincial convention, to be held at Boston, on September 22, to consider what measures should be adopted to obtain redress of these grievances.